2023
DOI: 10.1186/s13561-023-00425-y
|View full text |Cite
|
Sign up to set email alerts
|

The economic impact of anastomotic leak after colorectal cancer surgery

Abstract: Objective To determine the economic impact of the incremental consumption of resources for the diagnosis and treatment of anastomotic leak (AL) in patients after resection with anastomosis for colorectal cancer compared to patients without AL on the Spanish health system. Method This study included a literature review with parameters validated by experts and the development of a cost analysis model to estimate the incremental resource consumption o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The anastomotic leak in this study of 4.66% is lower than that reported in other large studies which range between 10 and 20% depending on the length of follow-up [ 3 , 23 ]. However, it is worth noting that some recent database studies have reported similar leak rates in the range of 3–8% [ 24 , 25 ]. One potential reason for this lower leak rate and limitation of our study is the inability to classify perianastomotic abscesses without signs of active leak as AL in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The anastomotic leak in this study of 4.66% is lower than that reported in other large studies which range between 10 and 20% depending on the length of follow-up [ 3 , 23 ]. However, it is worth noting that some recent database studies have reported similar leak rates in the range of 3–8% [ 24 , 25 ]. One potential reason for this lower leak rate and limitation of our study is the inability to classify perianastomotic abscesses without signs of active leak as AL in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The average DRG reimbursement for patients with AL covered only 86% of hospitalization costs, resulting in an average loss per patient with AL of €2041 [ 7 ]. In Spain, a recent study estimated the additional cost of diagnosing and treating AL following colorectal cancer surgery to be €38,819 for patients with colon cancer and €32,599 for patients with rectal cancer [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some bookkeepers-from a patient's point of view-also take increasing costs into consideration and perform an "economic evaluation from a societal perspective as a costeffectiveness and cost-utility analysis" [31,32]. Ultimately, and not surprisingly, number crunchers recently presented "the first cost-analysis study of AL after colorectal surgery" [63] in colorful pictures, and "concluded" that "the appearance of AL generates a considerable increase in the consumption of health resources, mainly due to an increase in hospital stays" and "the more complex the AL, the higher the cost associated with its treatment"-cost analyses on this topic have already been completed and are therefore obviously not an aim of our investigation.…”
Section: Reducing Costsmentioning
confidence: 99%